IMPACT OF THE GLOBAL FINANCIAL AND ECONOMIC CRISIS ON DEVELOPMENT: WHITHER AFRICA?. (November 2013) - Fosu, Augustin Kwasi; Lawson, David; Amann, Edmund
Abstract The global economic crisis beginning in 2008 has come at an inopportune time for Africa. Economic growth had recovered, poverty had declined, and human development had improved. Then the crisis hit. Growth then fell by 60 per cent. The growth decline has been less than in previous economic crises though. Africa's resilience currently likely results from improvements in economic and political governance and to changes in the external environment. It appears that Africa will once again resume its path towards prosperity. However, although low‐income and 'fragile' countries appear to be holding up well, many of them critically depend on external assistance. Above all, the commitment to improved governance must continue. Copyright © 2013 John Wiley & Sons, Ltd.